Development of Learning Evaluation With Monopoly Game Media on Financial Literacy Materials: Supporting SDG 4 Quality Education and Sustainable Development - Arlita Listiani; Riza Yonisa Kurniawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to develop and evaluate a Monopoly-based learning evaluation media, called EKOPOLI, to improve the financial literacy of 10th grade students at Driyorejo 1 State Senior High School. Method: This media was developed using the ADDIE model, which consists of the stages of needs analysis, design, development, implementation, and evaluation. Expert validation of the content and media indicates that EKOPOLI meets the criteria for validity and is suitable for use in learning. Results: The effectiveness of the media was tested by comparing students' learning outcomes before and after using the media, which showed a significant improvement in understanding and financial literacy skills. Additionally, the media was deemed highly practical by both teachers and students, confirming its ease of implementation and appeal in the learning process. The development of EKOPOLI also integrates sustainable development values in line with SDG 4's objectives on quality education and sustainable development. Research findings demonstrate that this Monopoly-based evaluation media is effective in enhancing understanding of financial literacy concepts and can support more engaging and contextual learning. Novelty: This study simultaneous applies the Theory of Planned Behavior (TPB) and the Thus, EKOPOLI has the potential to be widely adopted as an educational innovation that supports the achievement of quality education and the development of students' financial skills, preparing them to participate in sustainable development.